2016
DOI: 10.1103/physrevlett.116.101101
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Repeatedly FlaringδSunspots

Abstract: Active regions (AR) appearing on the surface of the Sun are classified into α, β, γ, and δ by the rules of the Mount Wilson Observatory, California on the basis of their topological complexity. Amongst these, the δ-sunspots are known to be super-active and produce the most X-ray flares. Here, we present results from a simulation of the Sun by mimicking the upper layers and the corona, but starting at a more primitive stage than any earlier treatment. We find that this initial state consisting of only a thin su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
(34 reference statements)
1
22
0
Order By: Relevance
“…Therefore, we need a systematic survey using flux emergence simulations to model these types of ARs (Toriumi et al 2014a;Fang & Fan 2015;Takasao et al 2015;Chatterjee et al 2016) and investigate their formation processes as well as the storage of magnetic energy (amount, place, etc.). In Figure 4, we found that S ribbon /S spot and |Φ| ribbon /|Φ| AR are larger for the CME-eruptive events, which may indicate the importance of the relative magnetic structure of the flaring region and the entire AR.…”
Section: Emergence Flares and Superflaresmentioning
confidence: 99%
“…Therefore, we need a systematic survey using flux emergence simulations to model these types of ARs (Toriumi et al 2014a;Fang & Fan 2015;Takasao et al 2015;Chatterjee et al 2016) and investigate their formation processes as well as the storage of magnetic energy (amount, place, etc.). In Figure 4, we found that S ribbon /S spot and |Φ| ribbon /|Φ| AR are larger for the CME-eruptive events, which may indicate the importance of the relative magnetic structure of the flaring region and the entire AR.…”
Section: Emergence Flares and Superflaresmentioning
confidence: 99%
“…Our analysis is centered on the numerical case study reported in Chatterjee et al (2016). For completeness, we briefly describe the salient points of the model setup here.…”
Section: The Mhd Modelmentioning
confidence: 99%
“…We test the concept of the weighted horizontal magnetic gradient (WG M ) method proposed by Korsós et al (2015, hereafter K15) by analyzing the emerging magnetic flux that generates a series of flares in the simulation, first reported in Chatterjee et al (2016).I nS e c t i o n2,w eb r i e fly outline the simulation setup and the numerical code used. In Section 3, we perform a detailed analysis of the flaring regions of the simulation in terms of ohmic heating and temperature increase for comparison of the findings with the WG M method given in Section 4.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations